To solve the expression \(\left(6^{-4}\cdot 8^{-7}\right)^{-9}\), we can use the properties of exponents.
-
Apply the exponent rule \((a \cdot b)^m = a^m \cdot b^m\): \[ \left(6^{-4} \cdot 8^{-7}\right)^{-9} = \left(6^{-4}\right)^{-9} \cdot \left(8^{-7}\right)^{-9} \]
-
Apply the exponent rule \(a^{-m} = \frac{1}{a^m}\) and also \(a^{m \cdot n} = a^{m \cdot n}\): \[ \left(6^{-4}\right)^{-9} = 6^{36} \quad \text{and} \quad \left(8^{-7}\right)^{-9} = 8^{63} \]
-
Therefore, we can combine these: \[ 6^{36} \cdot 8^{63} \]
So, the final equivalent expression is: \[ 6^{36} \cdot 8^{63} \]
Thus, the answer is Choice C: \[6^{36} \cdot 8^{63}\].